The general fault in our fault lines - Ruggeri, Kai; Većkalov, Bojana; Bojanić, Lana; Andersen, Thomas L; Ashcroft-Jones, Sarah; Ayacaxli, Nélida; Barea-Arroyo, Paula; Berge, Mari Louise; Bjørndal, Ludvig D; Bursalıoğlu, Aslı; Bühler, Vanessa; Čadek, Martin; et al. (Nature human behaviour, 2021)
Pervading global narratives suggest that political polarization is increasing, yet the accuracy of such group meta-perceptions has been drawn into question. A recent US study suggests that these beliefs are inaccurate and drive polarized beliefs about out-groups. However, it also found that informing people of inaccuracies reduces those negative beliefs. In this work, we explore whether these results generalize to other countries. To achieve this, we replicate two of the original experiments with 10,207 participants across 26 countries. We focus on local group divisions, which we refer to as fault lines. We find broad generalizability for both inaccurate meta-perceptions and reduced negative motive attribution through a simple disclosure intervention. We conclude that inaccurate and negative group meta-perceptions are exhibited in myriad contexts and that informing individuals of their misperceptions can yield positive benefits for intergroup relations. Such generalizability highlights a robust phenomenon with implications for political discourse worldwide.
Keywords: racionalizace; Group Processes; generalizace (psychologie); předsudek; sociální změna; Politics; Prejudice; Humans; sociální percepce; Communication Barriers; lidé; Rationalization; sociální chování; stereotypizace; Culture; kultura; Cross-Cultural Comparison; Sociological Factors; skupinové procesy; Social Perception; Generalization, Psychological; Social Behavior; sociologické faktory; srovnání kultur; Stereotyping; politika; Social Change; komunikační bariéry